2007 IEEE International Conference on Acoustics, Speech and Signal Processing - ICASSP '07 2007
DOI: 10.1109/icassp.2007.367044
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Signal-and-Link-Parametric Approach to Single-Ended Quality Measurement of Packetized Speech

Abstract: A hybrid signal-and-link-parametric approach to single-ended quality measurement of packetized speech is proposed. Transmission link parameters are used to determine a base quality for the test signal. The base quality is adjusted by degradation factors calculated from perceptual features extracted from the test signal. The degradation factors are based on KullbackLeibler distances between a parametric model trained online for the extracted features and reference models of normative speech behavior. The propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…ITU-T Recommendation P.563 represents the current state-of-art single-ended algorithm for traditional telephony applications [31]. Recent research, however, has suggested that P.563 performance is also compromised for VoIP applications [6]- [8]. In addition, the experiments described in Section III also suggest algorithm sensitivity to different VoIP connection parameters and high per-call estimation errors.…”
Section: B Objective Measurementmentioning
confidence: 94%
See 4 more Smart Citations
“…ITU-T Recommendation P.563 represents the current state-of-art single-ended algorithm for traditional telephony applications [31]. Recent research, however, has suggested that P.563 performance is also compromised for VoIP applications [6]- [8]. In addition, the experiments described in Section III also suggest algorithm sensitivity to different VoIP connection parameters and high per-call estimation errors.…”
Section: B Objective Measurementmentioning
confidence: 94%
“…Large may result in a model that overfits the training data, whereas small may result in models that are not accurate. Commonly, the approach taken is to try several values of and use the one that results in superior performance on an unseen test set [8]. Here, an alternate approach is taken and a recursive (greedy) EM algorithm is used.…”
Section: B Gaussian Mixture Reference Modelsmentioning
confidence: 99%
See 3 more Smart Citations